Frege on Identity and Co-Reference - Eros Corazza (Organon F, 2022)
In “Über Sinn und Bedeutung” (1892) Frege raises a problem concerning identity statements of the form a=b and he criticizes the view he holds in the Begriffsschrift (1879, § 8). In building on a suggestion by Perry (2001/12, ch. 7) I will show how Frege’s Begriffsschrift account can be rescued and how Frege’s 1892 criticism of his Begriffsschrift’s position somewhat miss the point. Furthermore, the Begriffsschrift’s view can be developed to account in quite an elegant way to the so-called Frege’s Puzzle without committing to the sense/reference (Sinn/Bedeutung) distinction Frege introduces in “Über Sinn und Bedeutung”. To do so we have, though, to give up the idea that all the relevant information conveyed by the utterance of a simple sentence is encapsulated into a single content. I will show of this can be done in adopting a Perry-style pluri-propositionalist model of communication.